Mechanical circulatory devices in acute heart failure. Issue 4 (August 2018) - Pineton de Chambrun, Marc; Bréchot, Nicolas; Combes, Alain
Abstract : Purpose of review: Temporary circulatory support (TCS) with short-term mechanical circulatory support (MCS) devices is increasingly used as a salvage therapy for patients with refractory cardiogenic shock. This article provides an overview of current devices, their indications and management, and discusses results of recent case series and trials. Recent findings: Percutaneous active MCS devices (Impella, TandemHeart…) and venoarterial extracorporeal membrane oxygenation (VA-ECMO) are utilized as a bridge to 'decision' that includes weaning after cardiac function recovery, transplantation, long-term MCS and withdrawal in case of futility. VA-ECMO is considered the first-line TCS since it allows rapid improvement in oxygenation, is less expensive, and is also suitable for patients with biventricular failure. Combining Impella or intra-aortic balloon pump support with ECMO might decrease left ventricular pressure and improve outcomes. Sepsis-associated cardiomyopathy, massive pulmonary embolism, arrhythmic storm and Takotsubo-like cardiomyopathy are among emerging indications for TCS. Summary: TCS have become the cornerstone of the management of patients with cardiogenic shock, although the evidence supporting their efficacy is limited. VA-ECMO is considered the first-line option, with a growing number of accepted and emerging indications. Randomized clinical trials are now needed to determine the respective place of different MCS devices in cardiogenic shock treatment strategies.